The efficacy of ethics management in Rustenburg local municipality - Maape, Neo (My University, 2017)
There is a general outcry among stakeholders that, despite the many efforts on the part of the South African government in the forms of laws and strategies to promote ethical behaviour and eradicate corruption, the situation in local government continues to deteriorate. Although a number of studies have been conducted on the problems of corruption and unethical conduct in municipalities, not much has been done to investigate the effectiveness of ethics management in local government. Following a qualitative and quantitative paradigm, this study sought to investigate the state of ethics management at Rustenburg Local Municipality by assessing the presence and effectiveness of ethics management using the pillars of the integrity management framework. The study revealed that, although the municipality has a code of conduct and policies in place, these are not fully implemented and enforced, and there are no development processes and structures in place. In brief, ethics management at the municipality is non-existent. The report presents a number of observations which include a call for the shift from the rule-based towards the value-based approach in the management of ethics. It argues that, in order to make the required impact, local government institutions must adopt a strategy that combines the rule-based and value-based approaches to the management of ethics. This would ensure that ethics are institutionalised and are no longer treated as taboos in the workplace.
A research report submitted to the Faculty of Commerce, Law and Management, School of Governance, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Management in Public Development and Management Johannesburg, 2017
Keywords: Public administration--Moral and ethical aspects--South Africa; Local government--Corrupt practices--South Africa